'Disastrologies'. Issue 2 (November 2017) - Schad, John
Abstract : 'Disastrologies' explores Derrida's fascination with dates and how that fascination reveals a secret correspondence, in every sense of the word, with Walter Benjamin – a man who has the same birth-date as Derrida. It is, though, the date of Benjamin's death and indeed its infamous mise-en-scène, the cheap hotel on the Franco-Spanish border, that dominates this text which takes the form of a dramatic monologue delivered by the hotel manager, Juan Suñer, a man known to be both a manipulator of dates and, indeed, close to the Gestapo. As the monologue unfolds, Suñer advances an elaborate calendrical re-reading of a host of Derrida texts which probes at the mystery not only of Benjamin's last night but also of living with both Jewish and Christian calendars. Finally, we see how this last of nights puts under unbearable pressure the infinite promise of both the Jewish Sabbath and the Christian Sunday.